Geometrijske in mehanske lastnosti celičnih metamaterialov - Novak, Nejc; Nečemer, Branko (2025)
Mechanical and Geometrical Properties of Cellular Metamaterials. The textbook entitled "Mechanical and geometrical properties of cellular metamaterials" is intended as study material for lectures on the course Design with Cellular Materials and Dimensioning of Lightweight Structures for students of the University of Maribor. The textbook is based on research into advanced metamaterials that combine unique mechanical and geometric properties. It contains an overview of modern cellular metamaterials and manufacturing technologies, the use of experimental and numerical approaches, and the results of mechanical and geometric characterisation research. The textbook's content is in accordance with the curricula of the mentioned subjects.
Keywords: cellular metamaterials; mechanical properties; geometrical properties; mechanical testing; computational simulations